Respuesta :
Answer:
c = 12
Step-by-step explanation:
3(c - 4) = 4(c - 6)
Use the distributive property on each side.
3c - 12 = 4c - 24
Now you need the terms with c on the left side and the numbers on the right side. Subtract 4c from both sides. Add 12 to both sides.
3c - 4c - 12 + 12 = 4c - 4c - 24 + 12
Combine like terms on each side.
-c = -12
Multiply both sides by -1.
c = 12
Answer:
c=12
Step-by-step explanation:
First things first, lets distribute. On the left side, you multiply the c-4 by 3, which comes out to 3c-12. On the right side, multiply everything inside the parenthesis by 4, which makes it 4c-24. So now you have 3c-12=4c-24. Now to simplify. We always stare with the numbers farthest away from the exponent, which in this case is -12 and -24. When simplifying, we always want to make it a positive number if possible to keep it easy. now, we add 24 to both sides (to cancel out the -24) which gives us 3c+12=4c. After that, we subtract 3c to both sides, which gives us 12=c, or c=12. Hope that helps!